2008
DOI: 10.1021/jo800885x
|View full text |Cite
|
Sign up to set email alerts
|

Planar Tetracoordinate Carbons in Cyclic Semisaturated Hydrocarbons

Abstract: A series of planar tetracoordinate carbon molecules in cyclic semisaturated hydrocarbons resulting from the combination of the C5(2-) skeleton with saturated hydrocarbon fragments is reported. The electronic stabilization and the bonding situation are studied through the analyses of molecular orbitals and the electron localization function. The magnetic properties are also revised, giving particular attention to the induced magnetic field. These systems are the first semisaturated cycles containing a planar te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
0
25
0
2
Order By: Relevance
“…[44] More isoelectronic analogues of the structures in Schemes 4a nd 5w ere designed by Sastry and co-workers. [45] Subsequently,M erino and co-workers [44,46] reported as eries of ptC-containing cyclic hydrocarbons (16 a-h; Figure 16). These molecules were created by combining the C 5 2À skeleton with cyclic hydrocarbon fragments.A lmost at the same time,E steves and co-workers [47] analyzed the spiropentadiene dication and concluded that the ptC is mainly stabilized by s electrons and that the ptC has an egative charge.T he total positive charge is spread along the skeleton structure.M oreover,t he spiropentadiene dication has a2 .3 kcal mol À1 activation barrier for ring opening.…”
Section: +mentioning
confidence: 98%
See 2 more Smart Citations
“…[44] More isoelectronic analogues of the structures in Schemes 4a nd 5w ere designed by Sastry and co-workers. [45] Subsequently,M erino and co-workers [44,46] reported as eries of ptC-containing cyclic hydrocarbons (16 a-h; Figure 16). These molecules were created by combining the C 5 2À skeleton with cyclic hydrocarbon fragments.A lmost at the same time,E steves and co-workers [47] analyzed the spiropentadiene dication and concluded that the ptC is mainly stabilized by s electrons and that the ptC has an egative charge.T he total positive charge is spread along the skeleton structure.M oreover,t he spiropentadiene dication has a2 .3 kcal mol À1 activation barrier for ring opening.…”
Section: +mentioning
confidence: 98%
“…[48][49][50] However,these "beautiful" planar 2À based hydrocarbons featuring ptC motifs. [46] The bond lengths are given in . (Reprinted with permission from Ref.…”
Section: Angewandte Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the delocalized ptCcontaining molecules composed of C, B, H atoms were also extensively studied [14][15][16][17][18][19][20][21][22][23][24][25][26]. The smallest organic molecule C 3 B 2 H 4 with ptC, proposed by Minyaev et al [18], can be served as a basic block to build an extended system such as the stable beltlike compounds (C 3 B 2 ) n H 4 (n = 2-6) and tubular compounds (C 3 B 2 ) n [25,31].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A very recent study shows that the incorporation of ptC into a saturated cyclic ring can also help to delocalize ptC's lone pair. 19 However, in all the known approaches so far, the delocalization of ptC's lone pair occurs only on the two-dimensional plane. A question may be raised: Why not stabilize ptC through three-dimensional electron delocalization?…”
Section: Introductionmentioning
confidence: 99%